Mitogen-Activated Protein Kinase CsPMK1 Is Essential for Pepper Fruit Anthracnose by Colletotrichum scovillei - Fu, Teng; Shin, Jong-Hwan; Lee, Noh-Hyun; Lee, Kwang Ho; Kim, Kyoung Su (Frontiers in Microbiology, 2022)
The phytopathogenic fungus Colletotrichum scovillei, belonging to the Colletotrichum acutatum species complex, causes severe anthracnose disease on several fruits including chili pepper (Capsicum annuum). However, the molecular mechanisms underlying the development and pathogenicity of Colletotrichum scovillei are unclear. The conserved Fus3/Kss1-related MAPK regulates fungal development and pathogenicity. Here, the role of CsPMK1, orthologous to Fus3/Kss1, was characterized by phenotypic comparison of a target deletion mutant (ΔCspmk1). The mycelial growth and conidiation of ΔCspmk1 were normal compared to that of the wild-type. ΔCspmk1 produced morphologically abnormal conidia, which were delayed in conidial germination. Germinated conidia of ΔCspmk1 failed to develop appressoria on inductive surfaces of hydrophobic coverslips and host plants. ΔCspmk1 was completely defective in infectious growth, which may result from failure to suppress host immunity. Furthermore, ΔCspmk1 was impaired in nuclear division and lipid mobilization during appressorium formation, in response to a hydrophobic surface. CsPMK1 was found to interact with CsHOX7, a homeobox transcription factor essential for appressorium formation, via a yeast two-hybridization analysis. Taken together, these findings suggest that CsPMK1 is required for fungal development, stress adaptation, and pathogenicity of C. scovillei.